Optical and Structural Study of the CZTS (Cu2ZnSnS4) Thin Film for Solar Cell Derived from the Chloride-Based sol-gel Precursor Solution (Dhaka University Journal of Science, 2022)
Fabrication of environmentally safe C2ZnSnS4 (CZTS) photovoltaic thin films of pure kesterite state is crucial. We have preparedCZTS thin films by sol-gel dip-coating process from chloride-based chemicals. After vacuum-annealed at 550°C, the optical andstructural characters of the films were further examined by UV–vis spectroscopy, X-ray diffraction (XRD), scanning electronmicroscopy (SEM), and energy dispersive X-ray spectroscopy (EDS) methods. The CZTS films offered high optical absorption(0.4x104cm-1) and nearly optimum bandgap energy (1.65e V). X-ray diffraction examination confirmed the kesterite structure offilms. Scanning electron micrograph affirmed the creation of jam-packed, condensed and granulated CZTS films. The thin filmdisplayed intermittent disposal of agglomerated particles with clear-cut edges. The energy dispersive X-ray spectroscopy study gavethe stoichiometric ratio as Cu: Zn: Sn: S= 2.2: 1.4: 1: 5.1.Dhaka Univ. J. Sci. 70(1): 1-7, 2022 (January)